Give Them Christ: Native Agency in the Evangelization of Puerto Rico, 1900 to 1917 - Santiago-Vendrell, Angel Daniel (Religions, 2021)
The scholarship on the history of Protestant missions to Puerto Rico after the Spanish American War of 1898 emphasizes the Americanizing tendencies of the missionaries in the construction of the new Puerto Rican. There is no doubt that the main missionary motif during the 1890s was indeed civilization. Even though the Americanizing motif was part of the evangelistic efforts of some missionaries, new evidence shows that a minority of missionaries, among them Presbyterians James A. McAllister and Judson Underwood, had a clear vision of indigenization/contextualization for the emerging church based on language (Spanish) and culture (Puerto Rican). The spread of Christianity was successful not only because of the missionaries but also because native agents took up the task of evangelizing their own people; they were not passive spectators but active agents translating and processing the message of the gospel to fulfill their own people’s needs based on their own individual cultural assumptions. This article problematizes the past divisions of such evangelizing activities between the history of Christianity, mission history, and theology by analyzing the native ministries of Adela Sousa (a Bible woman) and Miguel Martinez in light of the teachings of the American missionaries. The investigation claims that because of Puerto Rican agents’ roles in the process of evangelization, a new fusion between the history of Christianity, mission history, and theology emerged as soon as new converts embraced and began to preach the gospel.